Clinical Implications for Childhood Psychological Trauma and Mental Illness - Tadros, Eman; Daifallah, Nour (KMAN Counseling & Psychology Nexus, 2025)
Individuals with a mental illness are oftentimes stigmatized and untreated, especially children who are between the ages of six and 17. There is a complementary line of implication, between those who suffer from childhood trauma, and the correspondence between the development of mental illnesses. Oftentimes, children between these age ranges, who suffer with a mental illness, are involuntarily placed in institutions to try and maintain healthy behavior under supervision. The central purpose of this case application is to present an analysis of the definite correspondence regarding childhood trauma and the relations to mental health issues.